Enhancement of Lycopene Biosynthesis Using Self-Assembled Multi-Enzymic Protein Cages - Yulong Zhou; Yonghua Yao; Furong Zhang; Ning Yu; Binqiang Wang; Bing Tian (Microorganisms)
Constructions of self-assembled protein nanocages for enzyme immobilization and cargo transport are very promising in biotechnology fields such as natural product biosynthesis. Here, we present an engineered isopentenyl pyrophosphate (IPP) synthetic nanocage with multiple enzymes for lycopene production in bacteria. The enzymes involved in IPP biosynthesis (ScCK, AtIPK, and MxanIDI) were assembled onto the exterior of an engineered protein cage based on α-carboxysome. The IPP synthetic nanocage was co-expressed with CrtE/CrtB/CrtI in Escherichia coli. This approach increased the metabolic flux and resulted in a 1.7-fold increase in lycopene production in the engineered E. coli compared with the control strain. The results provide insights into the immobilization and assembling of IPP biosynthetic enzymes in protein nanocages, which serve as a powerful tool for achieving efficient synthesis of lycopene.